THE INFLUENCE OF TOURISM DEVELOPMENT ON FISHERMEN'S SOCIAL AND ECONOMIC LIFE IN LUMBAN VILLAGE BUL-BUL BALIGE DISTRICT TOBA SAMOSIR REGENCY NORTH SUMATRA PROVINCE - Manurung, Virgo Alexer; Hendri, Ridar; Darwis AN, Darwis AN (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Research on the influence of tourism development on social and economic life was carried out on July 7, 2018 until July 27, 2018 in the District of Toba Samosir, North Sumatra Province. This study aims to determine the effect of tourism development on social and economic life and identify the role of fishermen in tourism. The method used is a case study method that is carried out in a comprehensive and integrative manner in order to obtain an in-depth understanding of individual and theproblems he face. The results of this study indicate that the influence of the development of tourism on fishermen in Bul-bul Beach is the growth of new organizations to maximize tourism activities, increasing motivation in increasing income, as well as a culture that does not change with tourism, the influence on economic life of new jobs for the community in the field services and trade, the role of fishermen in the development of Bul-bul Beach tourism objects that are active in developing tourism potential. Keywords : Influence, Development, Tourism, Lumban Bul-bul